English Lessons at Elementary School in Japan Aimed at Improving Willingness to Communicate - Shinozaki, Fumiya; Sakashita, Mami (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
In this paper, we explore practical strategies to enhance willingness to communicate (WTC) among elementary school students during English lessons. The study focuses on creating a supportive environment that encourages interaction and fosters confidence in communication. The research also aims to investigate the impact of communication strategy (CS) instruction on students’ attitudes toward communication. Specifically, it examines changes in WTC and confidence levels among fifth-grade students. The methodology involved designing a series of English lessons centered around interaction. Activities included exchanging business cards, sending birthday cards, and discussing timetables. Pre- and interim-questionnaires collected data on students’ self-assessment and reflections. The study focused on six students who exhibited notable changes in attitudes. The results showed that many students enjoyed communicating their thoughts and learning about others. Confidence levels increased as students actively participated in interactions. Successful experiences were linked to the teaching of CS expressions. Moreover, acceptance of others’ contributions played a crucial role in creating a safe space for communication. The study’s implications highlight the importance of fostering an accepting attitude toward others’ communication. Teachers can promote confidence by emphasizing receptive responses. Overall, the research underscores the significance of creating a positive classroom atmosphere for language learning, ultimately empowering students to express themselves effectively in a foreign language setting.